IMPLEMENTASI IOT UNTUK EFISIENSI ENERGI LISTRIK: STUDI KASUS DI MASJID NASHRULHAQ, BANJARAN, KABUPATEN BANDUNG - Shafira Febriani; Muhamad Iqbal Dzulkarnaen; Anggi Cipta Lestari; Yolanda Georgia Andriani (Universitas Nusa Bangsa, 2026)
The efficiency of electrical energy use in public buildings such as mosques is often neglected due to lack of continuous technical supervision, which can lead to operational waste from negligence in turning off electronic devices. This community service activity aims to design and evaluate an Internet of Things (IoT)-based electrical energy monitoring and control system at the Nashrulhaq Banjaran Mosque using an ESP32 microcontroller. The system integrates ZMPT101B, ACS712, and DHT22 sensors for real-time acquisition of voltage, current, temperature, and humidity, with data visualized on the Blynk platform. During March–July 2025 implementation period, the system successfully collected 197,415 telemetry data entries. The evaluation results showed a weekly energy consumption of 2,814 kWh and a projected monthly operational cost of IDR 17,400 for the monitored load. With the remote-control feature, partners can instantly mitigate energy waste, potentially saving more than previous manual bills. Although data transmission reliability reached 100% (Packet Loss 0%), the Quality of Service (QoS) analysis recorded an average delay of 3,702.89 ms, indicating the need for further local network optimization to improve control responsiveness.